Description of three new species of Periga Walker from the Intervales State Park, Ribeirão Grande, São Paulo, southeastern Brazil and the resurrection of Automeris intermedius (Bouvier) (Lepidoptera: Saturniidae, Hemileucinae, Hemileucini) - Mielke, Carlos G. C.; Joerke, Elyana G.; Miranda, Aline V.; Costa, Jane (Zootaxa, 2017)
Three species of Saturniidae (Hemileucinae), all belonging to Periga Walker, 1855, are recognized as new and are described as: P. paranapiacaba sp. nov., P. faustinoi sp. nov., and P. intervales sp. nov. The Periga gueneei species-group is proposed to accommodate P. gueneei (Lemaire, 1973) and the new species P. intervales sp. n. described here. The status of another Saturniidae species is revised: Automeris intermedius (Bouvier, 1929), stat. rev., which is removed from the synonymy with A. nubila Walker, 1855. Habitus and illustrations of male genitalia are provided for all new species and both Automeris species. All holotypes are deposited in the Entomological Collection of the Oswaldo Cruz Institute, Rio de Janeiro, Rio de Janeiro, Brazil.